Consideration of Environmental Law Requirements in the Process of Local-Level Territory Planning - Kobetska, Nadiia (Український політико-правовий дискурс, 2025)
Given the relevance of issues related to the planning, organisation, development of territories and their broad, complex nature, this publication employs methods of analysis and synthesis as well as the transition from the abstract to the concrete to elaborate on specific aspects of integrating environmental law requirements into the process of territory planning at the local level. Based on the analysis of research findings, legislative provisions, urban planning practices and the content of certain approved territory planning documents, the article identifies the place of local-level territory planning within the system of the state regulation of territory planning; examines the specific features of reflecting environmental protection requirements and restrictions in certain types of urban planning documentation – namely, master plans of settlements and detailed plans of territories; outlines the significance of the fundamental environmental law instrument – strategic environmental assessment, through which environmental requirements are integrated into the preparation of plans and programmes; and characterises recent legislative amendments in the field of urban development related to the need for elaborating territorial recovery programmes, as well as mechanisms for integrating environmental considerations in their preparation. It is emphasised that environmental requirements and restrictions should be reflected at all levels of territory planning and in all types of urban planning documentation, including documentation at the local level. The article substantiates that an effective legal instrument for incorporating environmental law requirements into territory planning is strategic environmental assessment and highlights the particular importance of active public participation in the discussion of urban planning projects. Ensuring the consideration of environmental interests is essential through broad public discussion of the content of the new programmatic document introduced in 2022 – the comprehensive recovery programmes of an oblast or the territory of a territorial community (or part thereof).